Pathological response following neoadjuvant immunotherapy in mismatch repair-deficient/microsatellite instability-high locally advanced, non-metastatic colorectal cancer: Neoadjuvant checkpoint inhibition in locally advanced colorectal cancer. Issue 6 (4th April 2022) - Kothari, Anai; White, Michael G; Peacock, Oliver; Kaur, Harmeet; Palmquist, Sarah M; You, Nancy; Taggart, Melissa; Salem, Usama; Overman, Michael; Kopetz, Scott; Chang, George J
Abstract : This case series demonstrates an excellent pathological response to neoadjuvant checkpoint inhibitor (CPI) therapy in patients with mismatch repair-deficient (dMMR) colorectal cancer, which has translated into exemplary short-term oncological outcomes. As well as validating the utility of neoadjuvant CPI therapy in dMMR colorectal cancer, it also opens the door to future study of limited resection in patients with tumours that would otherwise require multivisceral resection.